The Material Science Behind Repetitive Hammering, Solution Annealing, and Tempering on Hadfield Steel - Rochim Suratman; Ida Farida (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The Hadfield steel used in this study contained 11 to 14% Mn and 1.1 to 1.4% C. Hadfield steel that underwent heat treatment showed insignificant differences in microstructure and hardness. On the other hand, Hadfield steel that was subjected to heat treatment combined with repetitive hammering exhibited changes in microstructure, as indicated by the presence of more and denser slip lines in accordance with an increased amount of deformation. The hardness value of the Hadfield steel also significantly increased. The slip lines discovered in the Hadfield steel that underwent solution annealing and tempering followed by repetitive hammering increased in number and appeared more compact than in the Hadfield steel without tempering. Additionally, the hardness value of the Hadfield steel with tempering was higher than that of the Hadfield steel without tempering. The strain values and thickness reduction results showed that the Hadfield steel subjected to tempering had higher strain and thickness reduction than the Hadfield steel without tempering. Higher strain and thickness reduction leads to higher hardness.